2020
DOI: 10.1002/jsfa.10841
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nitrogen practices on yield, grain quality, and nitrogen‐use efficiency of crops and soil fertility in three paddy‐upland cropping systems

Abstract: BACKGROUND Global food security faces a number of challenges due to increasing population, climate change, and urbanization, while excessive use of nitrogen fertilizers has become a major challenge for sustainable, intensive agriculture. Assessing the impact of agronomic management practices on seed yield, grain quality, and soil fertility is a critical step in understanding nutrientuse efficiency. RESULT The comprehensive evaluation index had good fitness to that of single attribute (i.e. seed yield, crop qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The pot experiment results proved coated CAN fertilizers as a possible option to improve nutrient use efficiency, reduce nitrogen losses, and minimize environmental pollution while providing nitrogen to plants more gradually during vegetation, which is also described by several authors [ 9 , 49 , 50 , 51 , 52 ]. The release of nitrogen from coated CAN fertilizers affected dynamic changes in the soil mineral N content during the vegetation of maize.…”
Section: Discussionsupporting
confidence: 73%
“…The pot experiment results proved coated CAN fertilizers as a possible option to improve nutrient use efficiency, reduce nitrogen losses, and minimize environmental pollution while providing nitrogen to plants more gradually during vegetation, which is also described by several authors [ 9 , 49 , 50 , 51 , 52 ]. The release of nitrogen from coated CAN fertilizers affected dynamic changes in the soil mineral N content during the vegetation of maize.…”
Section: Discussionsupporting
confidence: 73%
“…The application of controlled-release fertilizers (CRFs) is one way to improve nutrient use efficiency, reduce nitrogen loss, and contribute to minimizing environmental pollution, providing a better compromise among soil fertility, yield, and grain quality [ 20 , 21 , 22 ]. CRFs prove the potential to decrease the fertilizer application rate by 20% or 30% of the recommended value to achieve the same yield [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…29 Although numerous studies reported that N rates and application times strongly affect grain starch quality, only a few focused on the effects of slowrelease fertilizer. 16,30,31 Previous studies found that moderate N application rates are essential to improve grain yield and starch quality. 32,33 However, the effects of traditional and slow-release fertilizers on the physicochemical properties of waxy maize starch are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among maize types, waxy maize starch is composed of nearly pure amylopectin that endows it with high viscosity, high transmittance, high stability, and low retrogradation; hence, waxy maize starch is widely used in food and non‐food industries 29 . Although numerous studies reported that N rates and application times strongly affect grain starch quality, only a few focused on the effects of slow‐release fertilizer 16,30,31 . Previous studies found that moderate N application rates are essential to improve grain yield and starch quality 32,33 .…”
Section: Introductionmentioning
confidence: 99%